O espaço do conceito de “kizomba” (Studia Iberystyczne, 2019)
The Dimention of Space “kizomba”The popularity of kizomba nowadays is not questionable, but many who listen to it, who dance it and who enjoy it in some way, probably will not know that this rhythm has made a long way going through several continents over decades or even centuries. The goal of this communication is to travel in the world of kizomba, observing its origins and analyzing the transformations it faced until it turned up into a commercial product. We will try to describe the route that goes back to the so-called Black Atlantic and that apparently is still fruitful. So, at first, we’ll try to show how the colonial movement influenced a music genre that flourished in Africa. Then, how this rhythm (both as music and dance style) was relocated in Europe, where there was an attempt to recreate the original atmosphere, and its consequences. Afterwards, we’ll observe how the music was disseminated in the new location, and then how it worked as a starting point to a new transnational step, establishing kizomba not only as music genre but also as a dance style in a global context. Migration was the main engine for this voyage: from Black Atlantic to the recent migrations, there were many contributions to the dissemination and internationalization of kizomba.